Effects of supplemental feeding of feeds with different protein levels on the metabolism of the gut microbiota of bighead carp (Hypophthalmichthys nobilis) - Zheng Zhang; Junru Wang; Xiaomu Yu; Xiaoyu Zhou; Yanhong Wu; Jun Zou; Jingou Tong (Aquaculture Reports)
Conventional farming does not meet the future feeding conditions of bighead carp (Hypophthalmichthys nobilis) in high-density culture mode. The aim of this study was to investigate the effects of supplemental feeding of artificial protein feeds of different contents on the gut microbiome and metabolome of bighead carp in the traditional culture model. Bighead carp were fed with 30 % (LG, low protein group), 40 % (HG, high protein group) artificial protein feed and plankton only (PG, plankton group) for eight weeks, respectively. We used 16S ribosomal ribonucleic acid sequencing and liquid chromatography-mass spectrometry (LC-MS) techniques to study three groups of bighead carp. The results showed that the weight gain rate and specific growth rate were significantly increased in HG and LG compared to PG. There were significant differences in the abundance of gut microbiota among the three groups of bighead carp, such as increased Bacteroidota and Acetobacteroides (P < 0.05) in HG. In addition, metabolomic analyses of the three groups identified a total of 975 compounds. KEGG enrichment analyses showed that differential metabolites between the different groups were mainly enriched in the gastric acid secretion, vitamin B6 metabolism, arginine and proline metabolism, and tryptophan metabolism pathways. Overall, the addition of an artificial feed with a protein level of 40 % to traditional culture method promotes the amino acid metabolism in the gut microbiota of bighead carp and improves growth performance. These analytical data provide new insights for replacing the traditional culture mode and provide a theoretical basis for optimizing the composition of bighead carp feeds.